2022
DOI: 10.3389/fmed.2022.985955
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-1 as a severity biomarker for patients with trauma

Abstract: Tissue injury and hemorrhage induced by trauma lead to degradation of the endothelial glycocalyx, causing syndecan-1 (SDC-1) to be shed into the blood. In this study, we investigated whether serum SDC-1 is useful for evaluating trauma severity in patients. A single-center, retrospective, observational study was conducted at Gifu University Hospital. Patients transported to the emergency room for trauma and subsequently admitted to the intensive care unit from January 2019 to December 2021 were enrolled. A line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Syndecan-1 levels were higher in the isotrauma TBI group (SMD = 0.52; 95% CI = 0.03–1.00; I2 = 83%; P = 0.040), re-affirming previous findings that SDC-1 is elevated in trauma patients (23) (Fig. 2).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Syndecan-1 levels were higher in the isotrauma TBI group (SMD = 0.52; 95% CI = 0.03–1.00; I2 = 83%; P = 0.040), re-affirming previous findings that SDC-1 is elevated in trauma patients (23) (Fig. 2).…”
Section: Resultssupporting
confidence: 86%
“…Isotrauma TBI patients with higher SDC-1 level were at a higher risk of 30-day in-hospital mortality. This meta-analysis suggests that SDC-1 could be a biomarker of endotheliopathy and coagulopathy in TBI, a potential prognostic warning indicator for TBI, and re-affirmed previous findings that SDC-1 is elevated in trauma patients (23).…”
Section: Discussionsupporting
confidence: 87%
“…Multiple adult trauma studies have reported an association between syndecan-1 elevation and poor outcomes 22–24,35,36 . Gonzalez Rodriguez et al 22 reported a study of injured adults, defining a cutoff of 40 ng/mL as abnormal and comparing those with higher versus lower levels of syndecan-1; elevated levels were associated with higher injury severity as in this study, as well as mortality and the need for blood product transfusion.…”
Section: Discussionmentioning
confidence: 49%
“…[32][33][34] Multiple adult trauma studies have reported an association between syndecan-1 elevation and poor outcomes. [22][23][24]35,36 Gonzalez Rodriguez et al 22 reported a study of injured adults, defining a cutoff of 40 ng/mL as abnormal and comparing those with higher versus lower levels of syndecan-1; elevated levels were associated with higher injury severity as in this study, as well as mortality and the need for blood product transfusion. In a prospective study of 424 adult subjects, syndecan-1 was an independent predictor of <24-hour, 7-day, and 28-day mortality after controlling for other contributing factors including age, sex, ISS, Glasgow Coma Scale, base excess, platelet count, and hemoglobin.…”
Section: Discussionmentioning
confidence: 57%
“…Trauma and burns can result in strong pro-inflammatory host responses mostly driven by enormous amounts of circulating DAMPs with ensuing endothelial hyper-permeability and organ failure. Circulating levels of endothelial glycocalyx constituents in trauma are associated with adverse outcome [ 53 ].…”
Section: Question 5 What Are Explorative Tpe Indications For Critical...mentioning
confidence: 99%